Gut dysbiosis associates with cytokine production capacity in viral-suppressed people living with HIV - Zhang, Yue; Andreu-Sánchez, Sergio; Vadaq, Nadira; Wang, Daoming; Matzaraki, Vasiliki; van der Heijden, Wouter A.; Gacesa, Ranko; Weersma, Rinse K.; Zhernakova, Alexandra; Vandekerckhove, Linos; de Mast, Quirijn; Joosten, Leo A. B.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
People living with HIV (PLHIV) are exposed to chronic immune dysregulation, even when virus replication is suppressed by antiretroviral therapy (ART). Given the emerging role of the gut microbiome in immunity, we hypothesized that the gut microbiome may be related to the cytokine production capacity of PLHIV.To test this hypothesis, we collected metagenomic data from 143 ART-treated PLHIV and assessed the ex vivo production capacity of eight different cytokines (IL-1β, IL-6, IL-1Ra, IL-10, IL-17, IL-22, TNF and IFN-γ) in response to different stimuli. We also characterized CD4 + T cell-counts, HIV reservoir and other clinical parameters.Compared to 190 age-and sex-matched controls and a second independent control cohort, PLHIV showed microbial dysbiosis that was correlated with viral reservoir levels (CD4 + T cell-associated HIV-1 DNA), cytokine production capacity and sexual behavior. Notably, we identified two genetically different P. copri strains that were enriched in either PLHIV or healthy controls. The control-related strain showed a stronger negative association with cytokine production capacity than the PLHIV-related strain, particularly for Pam3Cys-incuded IL-6 and IL-10 production. The control-related strain is also positively associated with CD4 + T cell-level.Our findings suggest that modulating the gut microbiome may be a strategy to modulate immune response in PLHIV.